"Solidarity is our weapon": Social Mobilisation in Scotland in the Contest of the Post‐Political Condition. Issue 2 (22nd November 2018) - Mocca, Elisabetta; Osborne, Stephen
Abstract: The consensual climate of the post‐political order has been recently disrupted in Europe. The mass protests staged in different European countries and the resurgences of the extreme parties in response to the multiple European crises witness the "cracks" in consensual politics. While much of the scholarly attention has been drawn onto the socio‐political implications of large‐scale upraises, the contribution of bottom‐up sub‐national groups to the "return of the political" has been under‐researched. Therefore, this article focuses on sub‐national grassroots groups as instances of the "properly political" (Swyngedouw 2009, International Journal of Urban and Regional Research 33[3]:601–620). It is contended that these groups, by putting in place acts of solidarity, are "agonistic" political forms, containing in nuce the potential to counteract the post‐political order and to shape a new politics. To interrogate this argument, the article reports the findings of a case study analysis involving four grassroots groups based in Scotland.